Are Korean Industry-Sorted Portfolios Mean Reverting? - Seongman Moon (East Asian Economic Review (EAER), 2016)
This paper tests the weak-form efficient market hypothesis for Korean industry-sorted portfolios. Based on a panel variance ratio approach, we find significant mean reversion of stock returns over long horizons in the pre Asian currency crisis period but little evidence in the post-crisis period. Our empirical findings are consistent with the fact that Korea accelerated its integration with international financial market by implementing extensive capital liberalization since the crisis.
Keywords: G10; G11; G14; 330; Mean Reverting; Panel Variance Ratio Tests; Efficient Market Hypothesis; Industry-sorted Stock Price Indexes